Balancing the length of the distal tip by septins is key for stability and signalling function of primary cilia - Kanamaru, Taishi; Neuner, Annett; Kurtulmus, Bahtiyar; Pereira, Gislene (The EMBO journal, 2022)
Abstract Primary cilia are antenna-like organelles required for signalling transduction. How cilia structure is mechanistically maintained at steady-state to promote signalling is largely unknown. Here, we define that mammalian primary cilia axonemes are formed by proximal segment (PS) and distal segment (DS) delineated by tubulin polyglutamylation-rich and -poor regions, respectively. The analysis of proximal/distal segmentation indicated that perturbations leading to cilia over-elongation influenced PS or DS length with a different impact on cilia behaviour. We identified septins as novel repressors of DS growth. We show that septins control the localisation of MKS3 and CEP290 required for a functional transition zone (TZ), and the cilia tip accumulation of the microtubule-capping kinesin KIF7, a cilia-growth inhibitor. Live-cell imaging and analysis of sonic-hedgehog (SHH) signalling activation established that DS over-extension increased cilia ectocytosis events and decreased SHH activation. Our data underlines the importance of understanding cilia segmentation for length control and cilia-dependent signalling.
Published online 22 November 2021
Gesehen am 04.01.2023